2015 IEEE Virtual Reality (VR) 2015
DOI: 10.1109/vr.2015.7223466
|View full text |Cite
|
Sign up to set email alerts
|

Nested immersion: Describing and classifying augmented virtual reality

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. ABSTRACTWe present a system, intended for automotive design review use cases, that incorporates a tracked tablet in a CAVE, where both the tablet and the CAVE provide different views and interaction possibilities within the same virtual scene. At its core, this idea is not novel. However, the literature reveals few examples of this paradigm in which virtual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been suggested that physical awareness is important for effective interaction [27] in a VE. Therefore, some of the furniture and devices in the VE were mapped with corresponding objects in the real world ( Figure 3).…”
Section: The Ivar Methodsmentioning
confidence: 99%
“…It has been suggested that physical awareness is important for effective interaction [27] in a VE. Therefore, some of the furniture and devices in the VE were mapped with corresponding objects in the real world ( Figure 3).…”
Section: The Ivar Methodsmentioning
confidence: 99%